Generation of four-wave mixing with highly sharp idlers using 2 mm home-made side-polished fiber deposited by ZnO nanorod - Safaei, R.; Amiri, Iraj Sadegh; Sorger, Volker J.; Azzuhri, Saaidal Razalli; Rezaei, Mojtaba; Ahmad, Harith; Yupapin, Preecha Promphan (IOP Publishing, 2018)
A side-polished fiber with embedded zinc oxide nanorods (ZnO-NRs) is proposed, fabricated, and tested to generate four-wave-mixing (FWM). The side-polished fiber is manufactured by polishing a conventional single mode fiber to completely remove 2 mm of its cladding and its core partially, after which the fiber is simply immersed into a solution consisting of ZnO-NRs and allowing it to dry. A pump and a signal wavelength of 1550 and 1551 nm are injected into the fiber and generate idlers at 1549 and 1552 nm which agree well with theoretical values. Our experimental results show that the optimum FWM range is determined to be a 6 nm shifted away from the pump wavelength and occurs in the pump and wavelength spacing as narrow as 0.1 nm. The proposed system allows for the easy integration of optically active materials into a fiber.